Energetics and Kinetics Requirements for Organic Solar Cells to Break the 20% Power Conversion Efficiency Barrier - Oskar Sandberg (The Journal of Physical Chemistry C, 2021)
The thermodynamic limit for the efficiency of solar cells is predominantly defined by the energy band gap of the used semiconductor. In the case of organic solar cells, both energetics and kinetics of three different species play a role: excitons, charge transfer (CT) states, and charge-separated states. In this work, we clarify the effect of the relative energetics and kinetics of these species. Making use of detailed balance, we develop an analytical framework describing how the intricate interplay between the different species influences the photocurrent generation, recombination, and open-circuit voltage in organic solar cells. We clarify the essential requirements for equilibrium among excitons, CT states, and charge carriers to occur. Furthermore, we find that the photovoltaic parameters are determined not only by the relative energetics between the different states but also by the kinetic rate constants, highlighting the importance of slow exciton recombination at low energetic offsets. Finally, depending on the kinetic parameters, we find an optimal power conversion efficiency exceeding 20% at energetic offsets around 0.1 eV. These findings provide vital insights into the operation of state-of-art non-fullerene organic solar cells with low offsets.